Effectiveness of Pollutant Removal At the Wastwewater Treatment Plant in Goleniów - Jakubaszek, Anita (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article assesses the efficiency of pollutant removal at the sewage treatment plant in Goleniów after modernization of the technological system. The extension and modernization of the existing installation resulted from the need to adapt the treatment plant to accept larger loads of pollutants, improve the parameters of treated sewage discharged to the receiver, and the poor technical condition of the equipment.
Keywords: wastewater treatment; modernization; wastewater treatment plant; Wastwewater Treatment Plant in Goleniów; oczyszczanie ścieków; modernizacja; oczyszczalnia ścieków; Oczyszczalnia Ścieków w Goleniowie